2018
DOI: 10.1016/j.watres.2018.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of activated sludge-derived biochar determine the facilitating effects on Geobacter co-cultures

Abstract: Biochar has been reported to facilitate direct interspecies electron transfer (DIET) in co-cultures between Geobacter metallireducens and Geobacter sulfurreducens, a model defined co-culture system. In this study, the biochar derived from the activated sludge with different pyrolysis temperature was added to the co-cultures, the ethanol metabolism rates (Re) and succinate production rates (Rs) of co-culture with biochar-800 were 1.05- and 1.42-fold higher than that without addition. The results suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(28 citation statements)
references
References 64 publications
5
22
1
Order By: Relevance
“…However, similar to previous reports (Zhang et al, 2018), Geobacter could partially convert ethanol to acetate using GAC as insoluble electron acceptor (Fig. S5; Van Der Zee et al, 2003; Zhang et al, 2018), likely until it reaches its maximum capacitance of 40 F/g (Zhang et al, 2009). Co-cultures of G. metallireducens and M. horonobensis could not carry interspecies H 2 transfer because G. metallireducens is a strict respiratory microorganism which cannot ferment ethanol to generate H 2 (Shrestha et al, 2013) and because M. horonobensis is unable to use H 2 as electron donor for their metabolism (Shimizu et al, 2010).…”
Section: Resultssupporting
confidence: 89%
“…However, similar to previous reports (Zhang et al, 2018), Geobacter could partially convert ethanol to acetate using GAC as insoluble electron acceptor (Fig. S5; Van Der Zee et al, 2003; Zhang et al, 2018), likely until it reaches its maximum capacitance of 40 F/g (Zhang et al, 2009). Co-cultures of G. metallireducens and M. horonobensis could not carry interspecies H 2 transfer because G. metallireducens is a strict respiratory microorganism which cannot ferment ethanol to generate H 2 (Shrestha et al, 2013) and because M. horonobensis is unable to use H 2 as electron donor for their metabolism (Shimizu et al, 2010).…”
Section: Resultssupporting
confidence: 89%
“…Single species controls with GAC showed that ethanol could not be converted to methane by the methanogen or the syntroph alone ( Figure 6C and Figure S5). However, similar to previous reports (Zhang P. et al, 2018b), Geobacter could partially convert ethanol to acetate using GAC as insoluble electron acceptor ( Figure S5 ;Van Der Zee et al, 2003;Zhang P. et al, 2018b), likely until it reaches its maximum capacitance of 40 F/g (Zhang et al, 2009). Co-cultures of G. metallireducens and M. horonobensis could not carry interspecies H 2 transfer because G. metallireducens is a strict respiratory microorganism which cannot ferment ethanol to generate H 2 (Shrestha et al, 2013) and because M. horonobensis is unable to use H 2 as electron donor for their metabolism (Shimizu et al, 2010).…”
Section: Methanosarcina Horonobensissupporting
confidence: 93%
“…3, Fig. S3, S4, S5 and S6) further revealed that Geobacter cells were distributed on the MWCNTs aggregate surface rather than forming Geobacter aggregates as previously reported [18], yielding similar results to granular activated carbon (GAC), carbon cloth, and biochar added in the cocultures for accelerating DIET [12,17,21,22]. DIET enhancement effect of these materials was due to their excellent conductivity that supports electron transfer.…”
Section: Geobacter Adhesion On the Mwcnt Aggregatessupporting
confidence: 83%
“…Protein concentrations were determined by BCA method according to the manufacturer's protocol (Solarbio, China). Conductivity of the MWCNTs was determined with the four-probe method by a powder resistivity tester (ST2722, Suzhou Jingge, China) [17].…”
Section: Morphology and Measurement Of The Bacteria On The Mwcntsmentioning
confidence: 99%
See 1 more Smart Citation